# 1 Answer

# v=x-y/z

I don't know if I'm working this problem out right. If I'm wrong, someone help me out.

To get y by itself, multiply the other variables by z.

v * z = x * z - y

**vz = xz - y**

Add y to both sides.

y + vz = xz **- y + y**

** cancels out**

**y + vz = xz**

To get y by itself, subtract vz on both sides.

y +__ vz - vz__ = xz

**- vz**** cancels out**

y = xz - vz

**Answer: y = xz - vz**

4 years ago. Rating: 0 | |

### Top contributors in Mathematics category

### Unanswered Questions

pronounce exhilaration

Answers: 0
Views: 289
Rating: 0

In Phonetics and Phonology, what does the word «speech» mean?

Answers: 0
Views: 317
Rating: 0

what year did Lillian Bennett of Dillingham die?

Answers: 0
Views: 199
Rating: 0

amalgamation in terms of trade

Answers: 0
Views: 381
Rating: 0

What is community download?

Answers: 0
Views: 239
Rating: 0

what are hypolite in the body system

Answers: 0
Views: 229
Rating: 0

what is an ICT Asset

Answers: 0
Views: 387
Rating: 0

how do i plant roses

> More questions...
Answers: 0
Views: 345
Rating: 0